Comparative proteomic analysis of the telogen-to-anagen transition in cashmere goat secondary hair follicles - Han, Xiaoyu; Gao, Guizhen; Sun, Nanxiang; Dai, Bai; Ren, Liqing; Bai, Haobing; Liu, Jianing; Liu, Jie; Zhao, Hongyan; Liu, Dongjun (Frontiers in Veterinary Science, 2025)
Secondary hair follicles (SHFs) in cashmere goats produce high-value cashmere fibers, which cyclic regulation is critical for optimizing cashmere yield and quality. This study explores the phenotypic changes and differential protein expression profiles involved in the telogen-to-anagen transition of SHFs. Through histological observations, proteomic analyses, and immunohistochemical validation, we identified key molecular features and regulatory pathways underlying SHF cyclic renewal. Histological analysis showed that telogen-phase SHFs exhibit a reduced volume, decreased dermal papilla cell (DPC) and hair matrix cell (HMC) activity, compact structure, and superficial localization in the dermis. Anagen-phase SHFs exhibit significantly increased volume, deeper dermal penetration, and active cell proliferation. Proteomic analysis identified 3,654 proteins in skin samples, with 458 differentially expressed proteins (DEPs) significantly associated with biological processes such as cell adhesion, signal transduction, protein synthesis, and metabolism. These DEPs were enriched in key regulatory pathways, including Notch, Wnt, Jak–STAT, PI3K-Akt, and ECM-receptor interaction. Protein–protein interaction analysis identified A Disintegrin and Metalloproteinase Domain 17 (ADAM17), Secreted Frizzled-Related Protein 1 (SFRP1), and Protein Phosphatase 1 Catalytic Subunit Alpha (PPP1CA) as core regulators of SHF cyclic transitions. Validation by RT-qPCR, Western blot, and immunohistochemical analyses confirmed that ADAM17, SFRP1, and PPP1CA were predominantly localized in functional regions, including the outer root sheath (ORS), dermal papilla (DP), and hair matrix (HM). Their expression levels were significantly enhanced during anagen. ADAM17 is suggested to promote the growth of SHFs by regulating ORS cells proliferation and mediating signal transduction in DPCs, while SFRP1, as a modulator of the Wnt signaling pathway, likely supports SHFs growth and regeneration by modulating the activity of Secondary hair follicle stem cells (SHFSCs) and promoting the differentiation of HMCs. PPP1CA may enhance cell proliferation and metabolic activity by modulating phosphorylation states. In conclusion, this study identifies key molecular factors and pathways driving the telogen-to-anagen transition in cashmere goat SHFs. It emphasizes the roles of ADAM17, SFRP1, and PPP1CA in SHF renewal and offers insights into SHF development mechanisms and cashmere fiber improvement.